Geographic names and domain names - Lindsay, David (Journal of Telecommunications and the Digital Economy, 2014)
Review of Heather Ann Forrest, Protection of Geographic Names in International Law and Domain Name System Policy (2013, Wolters Kluwer) 339 pages including bibliography, tables and diagrams.